Non-transdermal microneedles for advanced drug delivery - Lee, KangJu (Adv Drug Deliv Rev, 2019)
Microneedles (MNs) have been used to deliver drugs for over two decades. These platforms have been proven to increase transdermal drug delivery efficiency dramatically by penetrating restrictive tissue barriers in a minimally invasive manner. While much of the early development of MNs focused on transdermal drug delivery, this technology can be applied to a variety of other non-transdermal biomedical applications. Several variations, such as multi-layer or hollow MNs, have been developed to cater to the needs of specific applications. The heterogeneity in the design of MNs has demanded similar variety in their fabrication methods; the most common methods include micromolding and drawing lithography. Numerous materials have been explored for MN fabrication which range from biocompatible ceramics and metals to natural and synthetic biodegradable polymers. Recent advances in MN engineering have diversified MNs to include unique shapes, materials, and mechanical properties that can be tailored for organ-specific applications. In this review, we discuss the design and creation of modern MNs that aim to surpass the biological barriers of non-transdermal drug delivery in ocular, vascular, oral, and mucosal tissue.